A Brief Approximation of The Issues of Accelerating and Deferring Zakat, with an Explanation of The Ruling and The Effect - Mohanad Mustafa Aqaileh; Ibrahim Abdalhaleem Obada (İslam Tetkikleri Dergisi)
.